A new species of freshwater crab of the genus Phallangothelphusa Pretzmann, 1965, from Colombia (Crustacea: Decapoda: Pseudothelphusidae) - Cardona, Luisa; Campos, Martha R. (Zootaxa, 2012)
A new species of Phallangothelphusa Pretzmann, 1965, is described from Cesar Department, Colombia, increasing thenumber of species in the genus to four: P. dispar (Zimmer, 1912), P. magdalenensis Campos, 1998, P. juansei Campos,2010, and P. martensis new species. The new species is distinguished from its congeners primarily by the morphology ofthe first male gonopod, specifically the greater curvature of the angle between distal and proximal projections of the mesialprocess, the shape of the distal projection and outline of the apex, and the orientation of the lateral process. An updated key for the identification of the species of Phallangothelphusa is given.